Pedagogic practice in company learning: the relevance of discourse - Höhns, Gabriela [Verfasser] (My University, 2018)
"In discussions of work-based learning in anglophone countries, a relatively new question concerns different learning opportunities for differentially positioned novices in the workplace. Basil Bernstein relates learners' positioning with respect to knowledge and within a community of knowers to variations in a discourse underlying and regulating the transmission. This article describes modalities of pedagogic practice in companies that give rise to such specific positionings of learners and discusses their relationship to a pedagogic discourse for company learning. It does so using the case of German company vocational education in the 'dual system', where a distinct macro-social pedagogic discourse underlies and regulates the transmission in companies. The data are drawn from problem-centred interviews with dual system graduates and analysed from a social-realist stance in relation to Bernstein's 'framing'. Although for Bernstein, who draws predominantly on school-based research, the control over 'framing' is always with the transmitters, this article points to instances of acquirers taking control in the data and traces them to the particular pedagogic discourse underlying German vocational education. The article points to further research possibilities with the goal of reconstructing, in a rule-directed way, an implicit discourse underlying company learning that lacks explicit macro-social discursive regulations." (author's abstract; BIBB-Doku)
Keywords: S 3.2 Unternehmen und Behörden; Betriebliche Berufsausbildung; Lernen am Arbeitsplatz; Lehr-Lern-Prozess; Auszubildender; Betrieblicher Status; Bildungstheorie; Beruflichkeit